2023
DOI: 10.1007/s00228-023-03495-3
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin reduces risk of heart failure rehospitalization in diabetic acute myocardial infarction patients: a propensity score-matched analysis

Abstract: Objective The aim of this study was to investigate the effect of dapagliflozin (DAPA) on the rate of heart failure rehospitalization in patients with acute myocardial infarction (AMI) and type 2 diabetes mellitus (T2DM). Methods AMI patients with T2DM from CZ-AMI registry between January 2017 and January 2021 were enrolled in this study. Patients were stratified into DAPA users and non-DAPA users. The primary outcome was the incidence of heart failure reho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…A total of 5 eligible studies encompassing 5398 patients (1576 in the SGLT2-I group and 3822 in the non-SGLT2-I group) were included in the pooled analysis [ 17 , 18 , 19 , 20 , 21 ]. All included studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 5 eligible studies encompassing 5398 patients (1576 in the SGLT2-I group and 3822 in the non-SGLT2-I group) were included in the pooled analysis [ 17 , 18 , 19 , 20 , 21 ]. All included studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 (Ref. [ 17 , 18 , 19 , 20 , 21 ]) presents a summary of the study and patient characteristics. The details of the risk of bias assessment of all eligible studies are provided in Table 2 (Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, CANVAS found that SGLT2i could lower risk of three-point MACE by 14% in 10,142 T2D patients who were at an elevated risk of CVD [ 25 ]. Recently, Mao L et al [ 26 ] reported that dapagliflozin could reduce risk of heart failure rehospitalization in diabetic acute myocardial infarction patients.…”
Section: Discussionmentioning
confidence: 99%